Economic Inequality in Ghana, 1891-1960 - Prince Young Aboagye; Jutta Bolt (African Economic History Network (AEHN), 2018)
This paper contributes to a growing literature on understanding drivers of pre-industrial inequality by constructing social tables for colonial Ghana. Ghana is generally perceived as fairly equal in terms of income distribution, both historically and today. We show, however, that income inequality rose rapidly during the colonial period, to inequality levels comparable to many contemporary African countries. We argue that the introduction and expansion of cocoa cultivation at the end of the 19th century in the forest belt of the country marked the most important development that shaped both national and regional inequality trends. Initial land abundance in the forest area provided opportunities for its population to engage in cocoa growing which increased the overall standards of living in the forest area. Areas where soil quality did not favour cocoa growing fell behind in terms of living standards, resulting in increasing national income inequalities from the 1930s onwards. Due to high set up costs of cocoa farms and increasingly polarized access to economic resources, only a wealthy minority was able to establish substantial cocoa farms, gaining much more than other social classes. The capital intensity of the export crop along with access to economic resources such as land seems an important factor driving inequality trends in Africa.
Keywords: N17; N37; N57; 330; Inequality; social tables; Ghana; economic history